Microemulsions for luminescent solar concentrator application. (1st March 2021) - Congiu, Annalisa; Gila, Liliana; Caccianotti, Luciano; Fusco, Roberto; Busto, Chiara; Zanardi, Stefano; Salvalaggio, Mario
Graphical abstract: Highlights: Quasi solvent free photoactive microemulsions. Matrix organization influences efficiency of LSCs based on microemulsions. Fluorescence quenching occurs due to confinement of the dye into microstructure. PL quantum yield and total internal reflection mainly affect device efficiency. constant efficiency for formulations with water content ranging from 20% to 70% Abstract: Luminescent Solar Concentrators (LSC) are devices designed to concentrate solar radiation into photovoltaic (PV) cells. Compared to the extensively studied solid ones, Liquid LSCs offer the advantage of easy replacement of the photoactive component but the main drawback, in perspective of large-scale applications, of the presence of solvents. We propose aqueous photoactive microemulsions as original active materials to overcome this limit. Both photophysics and microstructure of samples in the microemulsion area of the pseudo-ternary system Sodium Dodecyl Sulphate (SDS)/1-butanol/water/DTB (4, 7-Dithien-2-yl-2, 1, 3-benzothiadiazole) in toluene has been investigated. We detected a matrix structuring consistent with the dye-free microemulsions for scattering, conductivity, viscosity. The fluorophore does not alter the well-known self-assembling properties and thermodynamic stability. The impact of formulation on photoactivity, disclosed by fluorescence quenching, involves dye localization. The decrease in electrical efficiency when water content in microemulsions increases is lower than expected based on the reduction in the refractive index. The device performance results from the balance of many parameters. Hence the opportunity to produce more environmentally friendly liquid LSC's. Finally, the relevance of the key factors contributing to whole efficiency is addressed, within the limits of the small size device used in this study. A substantial prevalence of the photoluminescence quantum yield is observed, while the photon transport efficiency parameter results to be the least impacting parameter. The present study has given us the means to effectively control the formulation of microemulsion for LSC, identifying the parameters and the analytical techniques that are the most effective in their design phase.